Internet, E-commerce and E-government: Measuring the Gap between European Developed and Post-Communist Countries - Jovana Zoroja (Interdisciplinary Description of Complex Systems, 2011)
The paper analyses the extent to which information technology is used in European developed and post-communist countries. Indicators such as internet usage, e-commerce and e-government are used to measure the gap between European developed and post-communist countries. Special focus is given to the analysis of the difference in the level of education of male and female inhabitants who use internet, e-commerce and e-government services in European developed and post-communist countries.The main two assumptions of this paper are: (1) usage of information technology in three important areas: internet usage, e-commerce and e-government is lower in European post-communist countries than in developed countries and (2) male users with high level of education use information technology more than female users in European developed and post-communist countries. Lower usage and lower investments in information technology and also low level of education could be significant barriers towards further economic development of European post-communist countries.Data from European Statistics Database, section Information Society Statistics, were used during research for this paper.